SPATIO-TEMPORAL ANALYSIS OF MALARIA INCIDENCE ALONG HLAINGBWE TOWNSHIP IN MYANMAR AND THA SONG YANG DISTRICT IN THAILAND - Aung Minn Thway; Jaranit Kaewkungwal; Jetsumon Prachumsri; Siam Lawawirojwong; Tin Maung Hlaing; Thiha Myint Soe; Aung Thi; Chawarat Rotejanaprasert (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Malaria stays a serious public health problem in many countries of the world. The border regions are difficult to control for the malaria elimination due to the importation or reintroduction of malaria. A key to address such problem is reinforcing of surveillance activities with rapid identification. The objective of the study was to describe the malaria incidence rate and analyze the space and time distribution of malaria incidence rate in the high endemic border areas between Myanmar andThailand, the Hlaingbwe Township and Tha Song Yang District. Methodology: Daily malaria data were collected, using a passive surveillance system, from patients visiting local health facilities in both Tha Song Yang and Hlaingbwe regions. ArcMap software version 10.4.1 was used to describe the disease mapping of malaria incidence rate in both regions. Results: Compared to their counterparts, male gender had higher malaria incidence rates in both Tha Song Yang and Hlaingbwe regions. Non-Thai people had higher incidence rate than Thai in Tha Song Yang district. The higher incidence rates had seasonal pattern and the pattern was similar in both regions. The areas with a higher incidence rate could be seen in both inner side and along Thai- Myanmar border (upper and lower parts) in Tha Song Yang area. But in Hlaingbwe Township, the higher incidence rate occurred only in the inner and upper parts except for Me La Yaw and Tar Le areas which are situated along the Thai-Myanmar border. Along the border, the higher incidence rates were connected to the adjacent area in upper and lower parts between these two regions. Conclusion: The descriptive statistics and presented map in this study gave the health policy makers an important overview of malaria situation in this regions in order to intervene high risk areas more effectively, and distribute the resources in a useful manner.